Immunohistochemical features of endometrial stem cells: morphological aspects - Poslavska , O.V.; Shponka , I.S.; Khaskhachikh , D.A.; Potapov , V.O. (Морфологія / Morphologia / Morfologìâ, 2024)
Introduction. Menstruation is a unique biological phenomenon that occurs in a limited number of mammals such as humans and other higher primates. The endometrium changes dramatically depending on the phases of the menstrual cycle (ie, proliferative phase, secretory phase, and menstruation) and plays a critical role in the implantation of fertilized eggs. Purpose. To study the morphological and immunohistochemical features of endometrial stem cells with the study of the expression of ER, PgR, Ki67, CK PAN, PAX2, PAX8, PTEN markers that may have an impact on the development of endometrial hyperplasia. Methods. The work examines endometrial material obtained by diagnostic biopsy from 21 women with abnormal uterine bleeding (ABM). Primary monoclonal antibodies ER, PgR, CK PAN, Ki-67, PAX2, PAX8, PTEN and the UltraVision Quanto imaging system (LabVision) were used for IHC studies. Results. The endometrial glands of the deepest part of the basal layer during the menstrual cycle only weakly respond to estrogen stimulation and are completely insensitive to progesterone, which is very clearly visible in the control group (on the secretory endometrium) during an immunohistochemical study (IGH) with markers for estrogen and progesterone receptors. But the phenomenon of division of progenitor cells/stem cells can most clearly be traced to the phase of active proliferation, which also persists during hyperplastic processes in the endometrium. The expression of such specific markers as PAX2, PAX8, PTEN, of the control group was also detected in the basal layer of the hyperplastic endometrium, which confirms the homogeneity of the progenitor/stem cell phenotypes of the stroma and parenchyma. Conclusion. In the basal and functional layers of the endometrium, the difference in the expression of ER and PgR in the stroma and epithelial cells indicates a different way of activating the proliferation of reserve cells that may be involved in the processes of hyperplasia formation. The fact that the stroma actively responds to the hormonal signal of estrogen, while epithelial cells do not show sensitivity to estrogen, and the fact that the majority of stromal cells have a higher level of proliferation than the epithelium of the glands indicates a significant contribution of the influence of the stromal component to the formation of hyperplastic processes of the endometrium. The functional zone is a layer of the endometrium that undergoes cyclical changes depending on a woman’s menstrual bleeding. There is a regular renewal of cells that express CK PAN, PAX2, PAX8, PTEN, which remain typical markers of epithelial cells of the endometrium. The basal layer of the endometrium responds poorly to estrogen stimulation and is almost insensitive to progesterone, but continues to express CK PAN, PAX2, PAX8, PTEN, along with reserve cells.